Obesity as a Psychosomatic Syndrome - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Obesity is a psychosomatic syndrome. In this unique opinion piece, we describe the epidemic of obesity, and approach it from a psychosomatic perspective. We list the multiple causative, contributory, comorbid, complicating, confounding and curative aspects of obesity which require comprehensive psychosomatic addressal. The points discussed should be used as checklists for evaluation of person living with obesity. Keywords: Biopsychosocial model, mind body medicine, motivational therapeutics, obesity, overweight, person centred medicine.